Pengaruh Kebijakan Kinerja Dinas Pendidikan dalam Meningkatkan Kualitas Pendidikan di Kota Bandung - Shafira, Alifah; Shapira, Resma; Febriana, Salsa; Witska, Neng; Ariesmansyah, Andre (Universitas Pahlawan Tuanku Tambusai, 2025)
Education is an essential need for every individual who continues to adapt to the development of the times, technology, and culture. The quality of education is the foundation for forming the character of the next generation who are ready to face challenges. Law Number 20 of 2003 regulates the national education system to ensure equal opportunities, quality improvement, and relevance of education. In Bandung City, the Education Office has a vital role in improving the quality of education and forming competitive human resources. Policies and programs to improve the quality of education focus on budget management, curriculum development, improving teacher quality, and learning facilities. The challenges faced include the mismatch between the skills of educators and job needs, which can hinder the achievement of educational goals. Therefore, evaluation and improvement of policies are needed to produce better education.